2016
DOI: 10.1039/c6tb01210h
|View full text |Cite
|
Sign up to set email alerts
|

Agglutination of bacteria using polyvalent nanoparticles of aggregation-induced emissive thiophthalonitrile dyes

Abstract: A novel class of aggregation-induced emissive bis(phenylthio)phthalonitrile dyes were synthesized. These dyes assembled into nanoparticles that were equipped with mannose units. The nanoparticles underwent selective interactions with lectins and bacteria. The bright fluorescent aggregates aid in the visualization of the agglutination of bacteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 21 publications
0
28
0
Order By: Relevance
“…c) Structures of particle constructed from glycosylated thio‐phthalonitriles and representation of the aggregation between lectins/bacteria and the assembled particle. Reproduced with permission . Copyright 2016, The Royal Society of Chemistry.…”
Section: Carbohydrate‐conjugated Nanomaterialsmentioning
confidence: 99%
See 3 more Smart Citations
“…c) Structures of particle constructed from glycosylated thio‐phthalonitriles and representation of the aggregation between lectins/bacteria and the assembled particle. Reproduced with permission . Copyright 2016, The Royal Society of Chemistry.…”
Section: Carbohydrate‐conjugated Nanomaterialsmentioning
confidence: 99%
“…This system effectively targeted MDA‐MB‐231 cells overexpressing the mannose receptor (MR) for theranostics (Figure 17b). Mannosylated amphiphilic thio‐phthalonitriles were self‐assembled into AIE (aggregation‐induced emission)‐based particles in water, to interact with Con A (concanavalin A, mannose‐selective) and with the E. coli strain ORN178 over ORN208 based on selective bacterial aggregation, enabling their fluorescence detection (Figure 17c).…”
Section: Carbohydrate‐conjugated Nanomaterialsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, it was found that a simple tuning of emission wavelength can be obtained by variations of the substitution pattern as well as the introduction of different functional groups. Besides that, the self‐assembly of these compounds into micelles and rods as well as the application in molecular recognition of biomolecules was intensively investigated. Here we describe the synthesis of alkylated AIE emitters, including a detailed investigation of the photophysical properties in different solvents, the aggregation behavior as well as a detailed structure‐property relationship discussion based on X‐ray diffraction analysis data.…”
Section: Introductionmentioning
confidence: 99%